Pictorial health warnings on cigarette packs: Compliance and public understanding among adults in Malacca, Peninsular Malaysia / 'Ainun Mardhiah Meor Amir Hamzah - Ainun Mardhiah, Meor Amir Hamzah (2021)
Pictorial health warnings (PHWs) on cigarette packs, is one of the tobacco-free initiatives, targeting smokers and non-smokers. Since its implementation in Malaysia in 2009, little is known whether the PHWs on Malaysian cigarette packs comply with the PHW indicators, and well-understood by the public. Objectives: This study compared the prevalence of legal and illicit cigarettes in Malacca and the compliance level of PHWs with the Malaysian law and Framework Convention on Tobacco Control (FCTC) requirements between cigarette’s brands and variants, its legal status, types of Point of Sales (POS), and locations; also explored the public’s understanding and recommendations to improve the existing PHWs in Malaysia, among adults. Methods: This multi-mode research consisted of a quantitative and qualitative study. PHW compliance level of each cigarette pack was assessed using a modified protocol from the International Tobacco Pack Surveillance System (TPSS) involving 52 multi-types cigarette points of sale in urban and rural area in Malacca. Four Focus Group Discussions (FGDs) involving 24 adults (including non-smokers, smokers and ex-smokers) were conducted to elicit the public’s understanding and recommendations related to the existing PHWs. Data were analysed using the SPSS Ver 20.0 and Atlas.ti ver 8.0. Results: vii Of 121 variants of cigarettes, i) the majority of cigarettes obtained were legal cigarettes (83.5%), ii) 84.3% complied with the requirement to display the gazetted PHWs , iii) 94.2% complied with five requirement indicators, namely, having PHWs present on the packs, PHWs printed in full colour, PHW printed on the designated location, having the correct label elements and text elements & size, mainly contributed by legal cigarettes, iv) more than half of the cigarette variants showed a high compliance level to the overall 12 PHW indicators, contributed by the legal cigarette variants, those sold in the petrol stations, and in the urban areas ( p<0.05), v) The overall PHW compliance level and scores differ between cigarette brands and within variants of the same brand (not statistically significant), also between cigarettes legal status, types of POS and cigarettes sold in urban and locations (p<0.05), vi) Adults in this study easily understood PHWs showing effects on the lung and those related to oral health; contributed to early and frequent exposure of those effects via the education system, health programs conducted in school and social media. Gaps observed in the knowledge of smoking effects, misunderstanding, and misperceptions for PHWs, related explicitly to gangrene and pregnancy-related images. Our participants perceived the existing PHWs effective only to non-smokers and non-chronic smokers. vii) the existing PHWs in Malaysia were effective than those from other ASEAN countries. However, there were weaknesses arising from the images, form, contents, desensitisations of Malaysian PHWs, etc., that affect its impact. Conclusion: Legal cigarettes, those sold other than at grocery stores, viii and in the urban areas showed higher compliance with the requirements of both Malaysian law and FCTC. As the public were unable to comprehend the existing PHWs fully, the stakeholders need to actively address various aspects to strengthen and improve PHWs effectiveness in the future. Keywords: PHW, Compliance, Understanding, Effectiveness, Public.